GAYA KEPEMIMPINAN KEPALA DESA WONOSOCO KECAMATAN UNDAN KABUPATEN KUDUS DALAM RANGKA PEMBANGUNAN DESA YANG BERKEMBANG TAHUN 2013-2019 - Rohmah, Siti Nur; Astrika, Lusia (Journal of Politic and Government Studies, 2018)
Leadership style is a set of characteristics used by a leader to influence subordinates achieving organizational goals or can also be said that leadership style is often applied by a leader, such as giving orders, assign tasks, discipline, reprimand, communicate, and so forth. Wonosoco village is a village that has a leader who can build a more developed village. Successful development includes infrastructure development, community economy, and food security. Wonosoco village was originally just a small village with all its limitations and shortcomings on the economy and agriculture. However, since the village is led by Setiyo Budi who has open and transparent leadership all the limitations and shortcomings are improved. Due to the transfer of funds from the government and the village's original revenue (PADes), all the development went well. For a good performance in building Wonosoco village, Setiyo Budi was awarded as the best performing Village Head of sub-district level. There are various leadership styles, including democratic leadership styles, authoritarian styles, and freedom styles. From those several leadership styles, the researcher aims to explain which one approaches the leadership style of Setiyo Budi in leading Wonosoco Village. The research was conducted by using qualitative method with Descriptive-Evaluative type. Technique of collecting data is done by interview, documentation and literature study. The results show that Setiyo Budi's leadership is very good. The leadership style used by Setiyo Budi is a democratic style and an authoritarian style, in which the two styles are applied according to the conditions. Setiyo Budi also runs the role of village head well, such as the role of problem solver, the role of decision makers, the role of supervision, the role of information delivery, the role of motivator, the role influence, and the role communication relationship. Setiyo Budi is a democratic leader, as evidenced by his involvement of subordinates in every decision making. Suggestions that the author gives is a leader must establish a good relationship in leadership. Because the leader is a guardian and decision maker for whoever is led. Especially for a leader in governance in leadership will have an impact on society. Keywords: Leadership Style, Village Head, Development